Ordre du droit et droit de l'ordre - Zylberberg, Jacques (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
This essay undertakes a review of national and international law to demonstrate that law is mainly an ideological and variable instrument of the State and of the United Nations, which is a by-product of the states. In this perspective, the author opposes the pragmatical ideology of resistance against the sovereign state to the juridical legitimation and the behaviour of the States who reluctantly have conceded some civil and political rights. Those rights are endangered by the growing bureaucratization of the state, the inflation of the juridical norms and rules, in addition to the permanent repressive characters of the State. The criticism of the contradiction and the variation of the rule of law when it relates to "human rights" is also extended to international law as well as to the international organizations.